Touring Australia : [videorecording (DVD)] ; Touring New Zealand. (Questar, 2008)
Touring Australia brings home some of the world's greatest natural wonders, and most dynamic cosmopolitan cities. You'll visit Sydney, Melbourne, Brisbane, Darwin, Perth and Adelaide. Touring New Zealand is like a dream come true, visiting more than 100 sites on the North and South Islands.